Antibiotic Control of Mycoplasma in Tissue Culture - Perlman, D. (1967)
Seven of eight strains of Mycoplasma (PPLO) were found to be sensitive to the deoxystreptamines, certain macrolides, and the tetracyclines. These antibiotics are relative noncytotoxic. Kanamycin and tetracycline were useful in eliminating PPLO (pleuropneumonia-like organisms) strain Squibb no. 1 from a HeLa cell line which was deliberately contaminated with PPLO. Repeated exposure of M. laidlawii type B cells to neomycin resulted in a 50-fold increase in resistance, and the resistant strain was also resistant to gentamicin, kanamycin, neomycin, and paromomycin. A tetracycline-resistant strain of this culture was found to be resistant to 7-chlortetracycline, 7-chlor-6-demethyltetracycline, and 5-hydroxytetracycline. One PPLO strain, Squibb no. 2, derived from a contaminated HeLa cell culture, was resistant to all antibiotics studied.